2022
DOI: 10.1155/2022/6368765
|View full text |Cite|
|
Sign up to set email alerts
|

The Application of Nurse Stratified Management in Nursing Management

Abstract: Objective. To explore the application value of nurse stratified management in nursing management. Methods. One hundred nurses who worked in our hospital from June 2019 to September 2021 were recruited and assigned via the random number table method to an observation group (n = 50) and the control group (n = 50). The control group received routine nursing management, and the experimental group received stratified nursing management. The nursing quality, practice happiness, error rate, patient complaint, and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%